Solving conflicts outside the court system - Neugard, Trude Brita (The British journal of criminology, 1993)
Halvor is 27 years old. He lives and works in a medium-sized city in southern Norway. On the way home from a party one night before Christmas, Halvor broke into a store and vandalized it, emptying filing cabinest and shelves and shelves and generally making a mess. He did not, however, steal anything. After half an hour the police came and took Halvor into custody. During the ensuring interrogation, Halvor was unable to recall anything of what had happened. He remembered having been drinking but was not drunk. He only occasionally drinks alcohol. This was Halvor's first contact with the police and he was deeply sorry for what he had done. The next day Halvor called the owner of the store and apologized for what had happened. He asked if the owner would be willing to discuss the case with the Conflict Resolution Board. The owner was willing to do this. Damages were assessed at $1,100